2023
DOI: 10.1177/20363613231189984
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches for urachal cancer: Use of immunotherapy and targeted therapies

Abstract: Urachal cancer is a rare genitourinary malignancy that arises from the embryologic remnant of the urachus. The malignancy is considered to be aggressive, with no clear consensus on appropriate management for advanced disease. Although traditionally considered to be related to bladder cancer given its embryologic origin, several next generation sequencing studies have revealed the genomic profile of this genitourinary malignancy most closely resembles colorectal cancer. Moreover, these studies have identified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although there is no standardized protocol for urachal cancer, its treatment usually involves surgery and additional chemotherapy in some cases. Regiments 5-fluorouracil (5-FU) and FOLFOX (5-FU, oxaliplatin, and leucovorin) have both been described as effective in urachal cancer cases, which makes sense considering the similar profile of urachal cancer to CRC [10,18]. Indeed, next-generation sequencing studies have revealed that urachal cancer has a genomic profile that closely resembles that of CRC [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no standardized protocol for urachal cancer, its treatment usually involves surgery and additional chemotherapy in some cases. Regiments 5-fluorouracil (5-FU) and FOLFOX (5-FU, oxaliplatin, and leucovorin) have both been described as effective in urachal cancer cases, which makes sense considering the similar profile of urachal cancer to CRC [10,18]. Indeed, next-generation sequencing studies have revealed that urachal cancer has a genomic profile that closely resembles that of CRC [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regiments 5-fluorouracil (5-FU) and FOLFOX (5-FU, oxaliplatin, and leucovorin) have both been described as effective in urachal cancer cases, which makes sense considering the similar profile of urachal cancer to CRC [10,18]. Indeed, next-generation sequencing studies have revealed that urachal cancer has a genomic profile that closely resembles that of CRC [18]. This could be interesting because as previously discussed, CRC seems to be one of the cancers that is at increased risk in Crohn's disease patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation